Appreciation of peer reviewers for 2015. Issue 8 (18th April 2016) - Diffenbaugh, Noah; Beal, Lisa; Cardenas, M. Bayani; Cobb, Kim; Cronin, Meghan; Dombard, Andrew J.; Ilyina, Tatiana; Knorr, Wolfgang; Lavraud, Benoit; Newman, Andrew V.; Peterson, W.K. (Bill); Ritsema, Jeroen; et al.
Key Points: Appreciation of Peer Reviewers for 2015